Filippo Pennacchio, Il romanzo global. Uno studio narratologico (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2019)
Recensione di Filippo Pennacchio, Il romanzo global. Uno studio narratologico.